Along the road to crystal structure prediction (CSP) of pharmaceutical-like molecules. Issue 9 (17th February 2022) - Dudek, Marta K.; Drużbicki, Kacper
Abstract : In this Highlight the most important approaches in CSP to tackle molecular flexibility are characterized. Their successful use for drug-like molecules emphasizes the maturity of zeroth order CSP, while limitations indicate places for improvement. Abstract : Computational methods used for predicting the crystal structures of organic compounds are mature enough to be routinely used with many rigid and semi-rigid organic molecules. The usefulness of crystal structure prediction (CSP) is recognized not only by academia but also by the pharmaceutical industry, with an ability to accelerate the polymorph screening process and minimize the risk of unanticipated late-appearing polymorphs. The challenge, however, remains when molecules with high flexibility are considered. The same applies to high- Z ′ and/or multi-component crystal structures. This is because each degree of freedom causes an exponential rise in the number of structures that have to be evaluated, while often being nearly energetically degenerate. As a result, many researchers put a great deal of effort into aiding CSP of flexible and/or multi-component systems. In this work, a brief overview of the current capability of CSP methods to solve these issues is given, with a special emphasis on their application for pharmaceutical-like molecules.